Das kritisch-alternative pädagogische Milieu um 1968 Wissensbewegungen zwischen Handlungspraxis, Politik und Wissenschaft - Thole, Friederike (Beiträge zur Theorie und Geschichte der Erziehungswissenschaft, 2023)
The late 1960s can be described as a time of democratic awakening and social upheaval, also regarding discussions on education. Taking this period of critique and questioning as a starting point, the work proceeds to examine knowledge movements. Knowledge circulation and knowledge transformation processes between political and educational practice as well as educational theory are analysed on the basis of 9 biographical narratives of people who were active in educational or political practice projects around 1968. The first theoretical part of this thesis outlines the historical context and introduces the state of research on '1968 and pedagogy'. Subsequently, the thesis introduces its knowledge-historical theoretical approaches, from which the concept of knowledge movements developed for this thesis emerges. The first part of the thesis concludes with the presentation of the methodical and methodological premises, explains theoretically the applied procedure of an integrative coupling of discourses and biographies and shows the form of practical application in the work. The second part of the thesis includes the presentation of the empirical results and along inductively identified thematic strands, various aspects of new perspectives that can be considered as (co-)inspired/stimulated by the critical-alternative pedagogical milieu that are examined in greater detail. The third part of the paper presents the results and links them back to the theoretical premises. Thus, it is shown how knowledge of the discursive space of the critical-alternative pedagogical milieu changed through its discursive entanglements with the established educational science and how the established educational science entered a communicative process of opening through the confrontation with the new forms of knowledge. For educational science, the results and documented processes can thus can thus serve as a sample for contemplation and be referred to introspectively in the context of today's processes of theory formation or research. Disciplinary continuities and discontinuities were shown and hence it is possible to revise/identify trends or demarcations via the knowledge-historical findings of the work.